Penegakan Hukum Kasus Korupsi Dana Bos dan Peranan Badan Pemeriksa Keuangan (BPK) - Susilawati, Ni Putu Pebri; Saravistha, Deli Bunga; Aristiawan , I Gusti Ngurah (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2024)
School Operational Assistance, or BOSS, is one of the programs initiated by the government aimed at improving the quality of education, both means and supplies, as well as expropriation affairs. It is in accordance with the mandate given to the Fifth Path of the ideology of the nation, namely Pancasila, “Social Justice for All the People of Indonesia." Any budget-related program is highly vulnerable to corruption, so it needs to be monitored in its enforcement. According to Act No. 15 of 2006 on BPK, the financial audit of financial statements is carried out with the aim of giving sufficient assurance or reasonable assurance that the presentation of the report has been reasonably made in relation to all material matters in its substance, in accordance with the principles of accounting in general, such as the Central Government Financial Report. There are three principles to be met in the evaluation: continuity (continuity), comprehensiveness (comprehensiveness), and objectivity. For that, it felt important to raise the formula for the problem of how the arrangement of the management of the funds of the boss by the recipients should be channeled to the person entitled. How are criminal sanctions applied to recipients who commit fraud against the BOS Fund? And how is the supervisory mechanism used by the BPK as the authority to prevent the fraud of the BOS Fund from happening?